Investigasi Potensi Agregat Geoteknik Dengan Metode Geolistrik - Muhammad Rusli (PROMINE, 2015)
Geotechnical Aggregate are rocks that can be used as material for a wide range of constructionengineering purposes. The need for geotechnical aggregates increased along with the rapiddevelopment. Required sources of aggregate qualified engineering was good, close to the project siteand has large reserves. This research will be carried out an investigation to get to the source ofgeotechnical aggregate surveying of Geology and Geophysics measurements. Geophysicalmeasurement is working by using of Geoelctric methods with Schlumberger configuration. Geologicalsurvey result obtained is that the material consists of geotechnical aggregate are QTV , Qtvl and TMV ,composition form clastica volcanic rocks , breccias , lava , tuff andesite to basalt. Result ofGeoelectric measurements showed that the potential for geotechnical aggregate form Alluvial rockshaving resistivity values between 2-20 ohm meter , whereas the geotechnical aggregate form intrusiverocks is 30-80 ohm meter . Resource potential Probable amounted to 5,742,453 m3 .